Analysis of Factors Related to Diabetic Ulcer Patients’ Anxiety at Pasar Rebo Community Health Center East Jakarta - Rifiana, Andi Julia; Siti Maryam (Rajaki of Tulip Medika Publisher, 2025)
Background: Diabetes Mellitus is one of the leading causes of death in the world. In Indonesia, the number of DM sufferers reaches 19.47 million, with a prevalence of 10.6%. One of the serious complications of DM is diabetic ulcers. This condition not only causes perceptual disorders but also has psychological impacts, such as anxiety, that can worsen the patient's condition. Objective: To analyze factors related to anxiety in diabetic ulcer patients at the Pasar Rebo Health Center, East Jakarta. Methodology: The research design used quantitative with a cross-sectional approach. The research sample consisted of 40 respondents with diabetic ulcers who were treated at the Pasar Rebo Health Center. Data were collected using a questionnaire and analyzed using the Chi-Square test to determine the relationship between perception, environmental, and economic factors with patient anxiety. Results: The results of the study showed a significant relationship with the Chi-Square test and obtained data on perception factors with anxiety (p-value 0.04 <0.05) environmental factors with gold (p-value 0.008 <0.05), economic factors with anxiety (p-value 0.01 <0.05) in diabetic ulcer patients at the Pasar Rebo Health Center, East Jakarta. Conclusion: There is an influence between perception factors, environmental factors, and economic factors with anxiety in diabetic ulcer patients at the Pasar Rebo Health Center, East Jakarta. Suggestion: This study is expected to be a study material and library for further research on psychosocial factors that influence anxiety in diabetic ulcer patients.